Evaluation of the Jlantah Dam Inflowing Area as a Reference af Efficiency Towards Implementation Time and Cost - Sunawilalodra, Gaga; Maulana, Mahendra Andiek; Rohman, Arif (Journal of Social Research, 2023)
Jlantah Dam is located on the Jlantah River, Karanganyar Regency, Central Java Province. The construction of the Jlantah dam serves irrigation needs, raw water supply, flood reduction, and tourism. In the implementation of the construction, there are problems with land acquisition in the reservoir inundation area. This problem will affect the time and cost of implementing the construction of the Jlantah Dam. Therefore, it is necessary to carry out a simulation to determine the optimum reservoir volume of the reservoir that can fulfill the benefits of the dam, the implementation of which is not hampered by land acquisition in the inundation area and is efficient in terms of time and cost of implementation. In determining the inundation area of the reservoir, a capacity curve based on the topographic map is used to determine the area and volume of the reservoir at each elevation, then a simulation is performed to calculate at what elevation the reservoir can fulfill its planned utilization. The simulation was carried out with 2 (two) alternative conditions, namely the conditions at the crest elevation + 685 and the crest elevation + 682. From these two alternatives, it can be seen the reliability of the reservoir for each condition. The results of the evaluation obtained from the two mercury elevations have the greatest benefit value at + 685 elevations with a reservoir reliability value of 97.22%, a BCR value of 1.218, and an IRR value of 5.88% with a total cost of Rp. 1,750,818,179,096.